PENGARUH MEDIA PEMBELAJARAN VIDEO SENAM IRAMA TERHADAP KERJASAMA DAN KETEPATAN GERAK SENAM PGRI SISWA KELAS VII DI SMPN 1 LABANG - Mardiyana, Upik; Hartati, Sulis Janu; Isman, Soubar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In this study to determine the interaction of Rhythmic Gymnastics Video Learning Media on Cooperation and Accuracy of PGRI Gymnastics Movements of Class VII Students at SMPN 1 Labang. By using rhythmic gymnastics video learning media, it is hoped that students will be able to demonstrate cooperation and accuracy of movement towards PGRI Gymnastics material in class VII at SMPN 1 Labang. The sample used in this study was Class VII A of SMPN 1 Labang, each consisting of 32 students. Based on the recapitulation table, an increase in the value of the five aspects tested in experiments 1 to 4 was obtained. This study is strengthened by the analysis test conducted by the researcher which can be seen the t value = 5.463 with a significant value of 0.000 <0.05, then Ho is rejected and H1 is accepted with a significant value of 0.000 <0.05 which means there is a real (significant) increase in the Trust variable (X) against the Y variable.